M. Samarsky's artistic work on the topic of inclusion: modern reception - Sharova, T.; Sharov, Sergii; Шаров, Сергій Володимирович; Шаров, Сергей Владимирович; Karnachova, S. (My University, 2021)
EN: The article considers the issues of M. Samarsky’s artistic creativity, the peculiarities of adolescents with physical disabilities social adaptation on the example of the work “Rainbow for a friend”. The study provides a general analysis of the writer’s work. It was found out that M. Samarsky works closely with various publishers, publishes electronic and paper versions of his works, including Braille language. The list of books published by Ast, Exmo, Altaspera Publishing & Literary Agency Inc. is given. It was found that some writer’s works of art were published in digital format, including audio books. The importance of fiction on the topic of inclusion for the socialization of people with disabilities is emphasized. The analysis of M. Samarsky’s work “Rainbow for a Friend” is carried out. The study focuses on the work compositional features, indicates the thematic blocks with which you can orient yourself in the content of the literary text. It is revealed that the peculiarity of the work is the main character – a blind boy’s guide dog. The story is told by the first person. The content of the work contains the main character’s advice to people. This advice makes the reader respect animals and think about their actions. With the help of the dog’s voice there are frank hints on people who do not want to change themselves and lose the meaning of life. It is emphasized that the main character Sasha was almost disappointed in life. He does not have the opportunity to see all the beauties of life with his own eyes. The only friend and the adviser for the guy is the guide dog Trison. This interaction allows Sasha to cope with their problems and depressive mood. The work of art has a positive ending. Sasha has recovered from his blindness and can live a full life. At the same time, the guy does not need Trison’s help any longer. Therefore, he had to return Trison to the dog’ shelter. However, the author leaves the reader the right to guess about the future of the protagonist. The simple and clear language of the art work allows to read the text easily and to get acquainted with its subject matter. The presence of a significant number of reviews on the Internet indicates the relevance of the work and the positive emotions that arise in readers after their reading the story. UK: У статті розглядаються питання художньої творчості М. Самарського, особливості соціальної адаптації підлітків з фізичними вадами на прикладі твору «Веселка для друга». У дослідженні зроблено загальний аналіз творчості письменника. Виявлено, що М. Самарський тісно взаємодіє з різними видавництвами, друкує електронні та паперові варіанти своїх творів, у тому числі мовою Брайля. Подано перелік книг, що були видані у видавництвах «Аст», «Ексмо», “Altaspera Publishing & Literary Agency Inc.”. Виявлено, що окремі художні твори письменника видані у цифровому форматі, у тому числі аудіокниги. Наголошується на важливості художньої літератури на тему інклюзії для соціалізації людей з обмеженими можливостями. Здійснюється аналіз художнього твору М. Самарського «Веселка для друга». У дослідженні акцентовано увагу на композиційних особливостях твору, зазначено тематичні блоки, за допомогою яких можна зорієнтуватися у змісті художнього тексту. Виявлено, що особливістю твору є головний герой, яким виступає собака-поводир сліпого хлопця. Розповідь відбувається від першої особи. У змісті твору містяться поради людям від головного героя, які змушують читача поважати тварин, замислитися над своїми вчинками. Через вуста собаки лунають відверті натяки на людей, які не хочуть змінюватися та втрачають сенс життя. Наголошено на тому, що головний герой Сашко майже розчарувався у житті. Він не має можливості бачити всю життєву красу власними очима. Єдиним другом і порадником для хлопця є собака-поводир Трісон. Така взаємодія дає змогу Сашку впоратися зі своїми проблемами та пригніченим настроєм. Художній твір має позитивний відкритий фінал. Сашко прозрів та може жити повноцінним життям. Водночас Трісон більше не потрібний хлопцю, тому він повинен повернутися в притулок для собак. Однак автор залишає читачу право домислити подальшу долю головного героя. Проста та зрозуміла мова художнього твору дає змогу читачу з легкістю прочитати текст та проникнутись його тематикою. Наявність значної кількості відгуків в Інтернеті свідчить про актуальність твору та позитивні емоції, які виникають у читачів після його прочитання.
Художня творчість М. Самарського на тему інклюзії: сучасна рецепція
Keywords: artistic creativity; inclusion; limited possibilities; child; personality; художня творчість; інклюзія; обмежені можливості; дитина; особистість